Menumbuhkembangkan Sikap Toleransi Pada Anak Usia Dini: Implementasi Moderasi Beragama Di TK Dharma Wanita Bogokidul - Erfan, M. Ginanjar; Wahyuni, Putri Aprilia; Nikmah, Richa Mulin; Rahmawati, Silfiana Dewi; Mahfudhotin (Fakultas Tarbiyah IAIN Kediri, 2024)
Education in kindergarten is an important foundation in shaping children's character, including instilling the values of religious tolerance and moderation. This article reviews the implementation of religious moderation in a kindergarten where the majority of students are Muslim with a Christian minority in Bogokidul Village. The methods applied include various approaches such as multicultural picture stories, collaborative games, togetherness songs, and artistic creativity sessions. Through this approach, children are invited to understand and appreciate differences from an early age, with the hope of preventing the development of intolerant and radical attitudes in the future. The results of this implementation show that children are starting to understand the importance of mutual respect and cooperation regardless of religious differences. This article concludes that religious moderation can be taught effectively through simple and enjoyable methods, adapted to children's ages. This kind of education is important as a first step in creating a generation that is tolerant and able to live in diversity. Therefore, it is important for educators to integrate the values of religious moderation in the curriculum from an early age as an effort to prevent radicalism and intolerance.